2023
DOI: 10.3389/fcvm.2023.1097066
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with sacubitril/valsartan plus dapagliflozin in patients affected by heart failure with reduced ejection fraction

Abstract: BackgroundData about real-world effects of combined therapy with sacubitril/valsartan plus dapagliflozin in patients affected by heart failure (HF) with reduced ejection fraction (HFrEF) has not been widely reported. In this article, the benefits of dapagliflozin and sacubitril/valsartan respect to improvements of cardiac function in patients with HFrEF would be investigated.MethodsHF patients prescribed sacubitril/valsartan between January 2020 and January 2022 in a tertiary teaching hospital were selected us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…To achieve this, we included four recently conducted clinical trials, namely the EMPIRE-HF trial, the DAPA-HF trials, and the EMPEROR-Reduced trial, along with three retrospective studies. The retrospective studies conducted by Hsiao et al, 16 Jiang et al, 17 and Karabulut et al 18 examined the impact of the combination of SGLT2i and ARNI The meta-analysis of the studies included in this research indicates that the combination of SV and SGLT2i is superior in reducing all-cause mortality, cardiac death outcomes, and hospitalization incidence.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…To achieve this, we included four recently conducted clinical trials, namely the EMPIRE-HF trial, the DAPA-HF trials, and the EMPEROR-Reduced trial, along with three retrospective studies. The retrospective studies conducted by Hsiao et al, 16 Jiang et al, 17 and Karabulut et al 18 examined the impact of the combination of SGLT2i and ARNI The meta-analysis of the studies included in this research indicates that the combination of SV and SGLT2i is superior in reducing all-cause mortality, cardiac death outcomes, and hospitalization incidence.…”
Section: Discussionmentioning
confidence: 83%
“…To achieve this, we included four recently conducted clinical trials, namely the EMPIRE‐HF trial, the DAPA‐HF trials, and the EMPEROR‐Reduced trial, along with three retrospective studies. The retrospective studies conducted by Hsiao et al, 16 Jiang et al, 17 and Karabulut et al 18 examined the impact of the combination of SGLT2i and ARNI on patients with heart failure and reduced ejection fraction and DM. The studies concluded that this combination therapy was well‐tolerated among diabetic patients with HFrEF and was linked to a reduced risk of hospitalization due to heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have compared the efficacy of S/V and DAPA alone and in combination in post-MI patients with HF. A correlational investigation revealed that patients with HFrEF who received combination therapy with DAPA and S/V demonstrated notably enhanced cardiovascular benefits in comparison to those in individuals receiving monotherapy with S/V ( 31 ). In addition, the effects of the co-administration of S/V and DAPA surpassed those of monotherapy in protecting the rat myocardium against ischemia-reperfusion (I/R) injury ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have investigated the efficacy of sacubitril/valsartan combined with other medications in patients with CHF, but there are few data on the combination of this drug regimen with LBBP. 9 , 10 Therefore, we conducted a retrospective analysis of the clinical data of patients with CHF who received LBBP combined with enalapril or sacubitril/valsartan treatment in our hospital, with the aim of clarifying their specific intervention outcomes. We believe that our results may be useful as a reference for caregivers to select optimal treatment plans for their patients with CHF.…”
Section: Introductionmentioning
confidence: 99%